KOMUNIKASI RITUAL TAING HANG EMPO DI DESA WAESANO, KECAMATAN SANONGGOANG, KABUPATEN MANGGARAI BARAT - Sardi Duryatmo; Sarwititi Sarwoprasojo; Djuara Lubis; Didik Suharjito (Jurnal Penelitian Sosial Ilmu Komunikasi, 2023)
The people of Waesano Village, West Manggarai Regency, East Nusa Tenggara Province, practice a tradition known as taing hang empo, meaning 'to give, eat, and grandmother' in Manggarai. This ritual involves feeding the spirits of deceased ancestors, rooted in their belief in ancestral spirits, ata pali sina. This qualitative study utilizes ethnographic communication methods to explore the taing hang empo ritual and its significance in the village, drawing on Creswell's perspective of qualitative research as a practice to interpret the world. Employing Carey's concept of ritual communication, this research delves into the communication patterns during taing hang empo, highlighting shared cultural participation, the sacredness of activities, symbolic language use, and the conveyance of messages through unique communication symbols. Data collection involved in-depth interviews and observations, particularly during nemba bongot, an epidemic affecting villagers and livestock. During such crises, the community seeks assistance from ancestral spirits, triggering ritual communication resembling a sacred ceremony. This study illuminates non-professional, belief-based rituals, depicting micro-scale practices related to specific beliefs or religions. Post-ritual, ancestral spirits reportedly communicate medicinal plant remedies for the sick through dreams. This research offers insight into the role of ritual communication and its impact on addressing communal challenges in the village.